MATHEMATICAL MODELING OF HEAT SUPPLY SYSTEMS - Madaliyev Erkin Urinbayevich; Tillaboyeva Farangiz Shavkatjon kizi (Web of Journals Publishing, 2025)
This article highlights the importance of mathematical modeling methods in order to increase the energy efficiency of heat supply systems in buildings and structures. To reduce heat energy consumption, the possibilities of analyzing the temperature regime and simulating heat transfer processes are analyzed based on various physical and mathematical equations. Also, ways to achieve an optimal energy balance are considered, taking into account the thermal parameters of construction structures.
Keywords: Heat supply, mathematical modeling, energy efficiency, heat balance, heat transfer, construction structure, temperature regime, simulation, convection, thermal coefficient.